2017
DOI: 10.1177/2048872617700874
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia and inflammation in acute decompensated heart failure: a registry-based analysis of 1939 patients

Abstract: Pneumonia is relatively common in ADHF and a predictor for in-hospital mortality. However, inflammation in general seems to be more important than pneumonia itself for long-term prognosis. Compared to community-acquired pneumonia studies, C-reactive protein levels were rather low and therefore pneumonia might be over-diagnosed in ADHF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 31 publications
4
24
0
Order By: Relevance
“…This association of CSI with hemodynamic data emphasizes the mechanistic plausibility of our results. Recent registry data have shown that approximately 20% of patients hospitalized for AHF had concomitant lung diseases such as pneumonia and COPD [35][36][37], and these patients generally excluded in previous reports assessing the diagnostic value of CXR [16,17,38,39]. However, our subgroup analysis provided a remarkably homogenous diagnostic performance of CSI across various subgroups (i.e., elderly and BMI) and coexisting lung diseases (i.e., COPD and pneumonia).…”
Section: Discussionmentioning
confidence: 74%
“…This association of CSI with hemodynamic data emphasizes the mechanistic plausibility of our results. Recent registry data have shown that approximately 20% of patients hospitalized for AHF had concomitant lung diseases such as pneumonia and COPD [35][36][37], and these patients generally excluded in previous reports assessing the diagnostic value of CXR [16,17,38,39]. However, our subgroup analysis provided a remarkably homogenous diagnostic performance of CSI across various subgroups (i.e., elderly and BMI) and coexisting lung diseases (i.e., COPD and pneumonia).…”
Section: Discussionmentioning
confidence: 74%
“…14 Further evidence for a role of inflammation in the pathogenesis of acute heart failure comes from a large registry that assessed the prognostic impact of pneumonia and signs of systemic inflammation in patients with acute heart failure. 15 In this registry pneumonia was relatively common but inflammation in general seemed more important than pneumonia itself for long-term prognosis as only C-reactive protein was an independent predictor for long-term mortality.…”
mentioning
confidence: 89%
“…8 Inflammation diagnosed by C-reactive protein during pneumonia was independently associated with in-hospital and long-term mortality. 6 Experimental data indicated that pulmonary congestion may facilitate the growth of bacteria commonly seen in pneumonia. 6 Also, pulmonary congestion was identified as an independent predictor of pneumonia.…”
Section: Laboratory Datamentioning
confidence: 99%